Pursuit of Investment Portfolio Adequacy - Rutkauskas, Aleksandras Vytautas; Rutkauskas, Vytautas (Ekonomika, 2000)
The article deals with the role of the modern investment theory in development investment ideology and practice altogether with the problems modern investment theory encounter on its way of self-perfection.Uncertainty of future profit possibilities for separate assets or portfolio of these assets requires for adequate investment portfolio to account non-deterministic feature of future possibility. Such kind of investment portfolio is presented in the paper altogether with some imitative approach for practical construction of such models as well as numerical solution of the model.The proposed adequate investment portfolio model was tested for assessment impact of enlargement of self-dependency or independence between portfolio assets on the shape of efficiency zone and its main characteristics.Use of the adequate investment portfolio model in practice shifts from employment of efficiency line and indifference curve to make use of efficiency zone and investors utility functions. The new approach in construction and exploitation of investment portfolio ought to widen modem investment theory possibilities and supply new quality for investment analysis and management when the processes are under the risk and uncertainty.